Factors preventing the adoption of agricultural technology among banana and plantain growers: A mapping review of recent literature - Nalini, Arumugam; Balogun Daud, Ishola (2019)
It is believed that improved agricultural technology adoption, such as using improved seed varieties, fertilizer application could stimulate the changeover from the presently low productivity, peasant, and subsistence farming to commercial farming which is able to produce surpluses. However, the rate of adoption of these technologies in developing countries has remained low. This paper aims at shedding some light on the potential factors that preventing agricultural technology adoption among Banana and Plantain growers. It does so by reviewing previous studies done on technology adoption. Technological, economic, institutional factors and social factors are found to be the determinants of agricultural adoption. Therefore, this review paper has the aim to identify the factors preventing the adoption of Agricultural technology in recent Literature. Twenty articles were selected from (2013 onward) upon screening and mapping review was conducted. The reviewed paper on adoption to widen the range of variables used by including Subsidy policy and cost of technology towards new technology.